International classification of abdominal wall planes (ICAP) to describe mesh insertion for ventral hernia repair. Issue 3 (25th December 2019) - Parker, S G; Halligan, S; Liang, M K; Muysoms, F E; Adrales, G L; Boutall, A; Beaux, A C; Dietz, U A; Divino, C M; Hawn, M T; Heniford, T B; Hong, J P; et al.
Abstract: Background: Nomenclature for mesh insertion during ventral hernia repair is inconsistent and confusing. Several terms, including 'inlay', 'sublay' and 'underlay', can refer to the same anatomical planes in the indexed literature. This frustrates comparisons of surgical practice and may invalidate meta-analyses comparing surgical outcomes. The aim of this study was to establish an international classification of abdominal wall planes. Methods: A Delphi study was conducted involving 20 internationally recognized abdominal wall surgeons. Different terms describing anterior abdominal wall planes were identified via literature review and expert consensus. The initial list comprised 59 possible terms. Panellists completed a questionnaire that suggested a list of options for individual abdominal wall planes. Consensus on a term was predefined as occurring if selected by at least 80 per cent of panellists. Terms scoring less than 20 per cent were removed. Results: Voting started August 2018 and was completed by January 2019. In round 1, 43 terms (73 per cent) were selected by less than 20 per cent of panellists and 37 new terms were suggested, leaving 53 terms for round 2. Four planes reached consensus in round 2, with the terms 'onlay', 'inlay', 'preperitoneal' and 'intraperitoneal'. Thirty-five terms (66 per cent) were selected by less than 20 per cent of panellists and were removed. After round 3, consensus was achieved for 'anterectus', 'interoblique', 'retro-oblique' and 'retromuscular'. Default consensus was achieved for the 'retrorectus' and 'transversalis fascial' planes. Conclusion: Consensus concerning abdominal wall planes was agreed by 20 internationally recognized surgeons. Adoption should improve communication and comparison among surgeons and research studies. Graphical Abstract: Current nomenclature for abdominal wall planes is inconsistent; this confuses clinical practice and frustrates comparative studies. A Delphi study was performed, involving 20 international hernia experts, to define abdominal wall planes precisely. Via consensus, an international classification of abdominal wall planes was established. Order created by consensus